Revealing Cultural Causes of Fraud: An Ethnographic Study in Public Company - Dinata, Ruri Octari; Irianto, Gugus; Mulawarman, Aji Dedi (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2018)
Abstract: Revealing Cultural Causes of Fraud: An Ethnographic Study in Public Company. This ethnographic study aimed to reveal the cultural causes of fraud in public company. The data was obtained from direct observation and interview to the research site at Public Company X, located in Medan City of North Sumatra. This study found that existence of a culture of